2015
DOI: 10.3402/tellusa.v67.25950
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two modified Kalman gain algorithms for radar data assimilation in the WRF model

Abstract: A B S T R A C TThis work attempts to validate two modified Kalman gain algorithms by assimilating a single radar simulation data set into the Weather Research and Forecasting model using an Ensemble Square Root Filter. Emphasis is placed on the comparison of assimilation performance between the two modified algorithms against the classical Kalman gain algorithm when the measurement operator is non-linear. Three ideal storm-scale experiments, which are configured identically except for the different Kalman gain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…( 10) reduces the analysis error of reflectivity by approximately 2 dBZ in our early test (not shown). This result is consistent with that of Yang et al (2015).…”
Section: The Observation Operatorsupporting
confidence: 92%
See 1 more Smart Citation
“…( 10) reduces the analysis error of reflectivity by approximately 2 dBZ in our early test (not shown). This result is consistent with that of Yang et al (2015).…”
Section: The Observation Operatorsupporting
confidence: 92%
“…Tang et al (2014) demonstrated that this alternative could lead to better results. Furthermore, Yang et al (2015) examined the application of this alternative in radar DA and showed that the alternative approach produced lower analysis errors for the model variables associated with radial velocity (three wind components) and reflectivity (mixing ratios of rain, snow, and graupel). Given that remote sensing observations such as those obtained by radars and satellites are important parts of a multiscale observation network, Local DA adopts the alternative approach proposed by Tang et al (2014).…”
Section: The Observation Operatormentioning
confidence: 99%